Fourth-generation Ceramic Head Fracture in Total Hip Arthroplasty: A Case Report and Literature Review - Clark Yin, MD; Lauren Eberhardt, MD; Matthew Cederman, BS; Henry Haley, MD; Andrew Steffenmeier, MD; Mark Karadsheh, MD (Arthroplasty Today)
Ceramics are used in total hip arthroplasty due to inherent wettability and low wear rates, but fracture risk is a known complication. Rates as high as 13.4% were reported in the past, yet as low as 0.02% in newer generations. Howard et al. reported a fracture rate of 0.009% for fourth-generation ceramic heads. We present a case report of a 69-year-old male with a BMI of 40.01 kg/m2 who suffered a fracture of a 36-mm ceramic femoral head with pseudoacetabular involvement of the polyethylene liner. This occurred 2 years and 3 months after his primary surgery after a 4-foot fall off of a ladder. The patient underwent revision of his total hip arthroplasty with arthroplasty of the polyethylene liner and femoral head component without stem explantation.